(untitled) (Global Journal of Science Frontier Research, 2014)
The study was conducted to assess the effects of graded levels of browse forage (Balanites aegyptiaca) leaves inclusion in the diets of growing rabbits on haernatological and biochemical indices. Five diets were formulated, treatment 1(control), 2 3 4 and 5 in which Groundnut haulm was replaced with Balanites aegyptiaca at 0%, 5%, 10%, 15%, and 20% respectively. Thirty (30) four weeks old weaner rabbits of different breeds (chinchilla x California x New Zealand) used for the experiment were allotted to the five treatments (T1, T2, T3, T4, and T5) with two rabbits per replicate and six rabbits per treatment in a randomized complete block design. The trial lasted for 9 weeks. Effects of the diets on haematology and serum chemistry were elicited on the results. The result shows that Balanites aegyptiaca supplementation at these levels had no adverse effect on red blood cell counts, white blood cell counts, packed cell volume and haemoglobin. All the parameters differ significantly (P